2014
DOI: 10.1093/jac/dku245
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance, genetic resistance determinants for ceftriaxone and molecular epidemiology of Neisseria gonorrhoeae isolates in Nanjing, China

Abstract: Ceftriaxone, ideally 500 mg and together with azithromycin (1-2 g), should be recommended for treatment of gonorrhoea in Nanjing, China. However, N. gonorrhoeae strains with resistance to ceftriaxone have been found in Nanjing. NG-MAST and ceftriaxone resistance determinant analysis can be valuable to supplement the antimicrobial resistance surveillance in China, which needs to be further strengthened.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 34 publications
2
30
0
1
Order By: Relevance
“…In the present study, we found that the proportion of N. gonorrhoeae isolates with CRO MICs ≥ 0.125 mg/L in Shanghai (1996–2013) greatly varied from year to year, ranging from 0% (1995) to 19.72% in 2008, and 13.76% in 2013. Our findings were consistent with those of a survey of CRO susceptibility in Nanjing, China [ 24 ],[ 25 ]. The proportion of CRO less susceptible N. gonorrhoeae isolates (CRO MIC ≥ 0.06 mg/L) was 17.86–50.5% during the period from 1999 to 2006 in Nanjing [ 24 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, we found that the proportion of N. gonorrhoeae isolates with CRO MICs ≥ 0.125 mg/L in Shanghai (1996–2013) greatly varied from year to year, ranging from 0% (1995) to 19.72% in 2008, and 13.76% in 2013. Our findings were consistent with those of a survey of CRO susceptibility in Nanjing, China [ 24 ],[ 25 ]. The proportion of CRO less susceptible N. gonorrhoeae isolates (CRO MIC ≥ 0.06 mg/L) was 17.86–50.5% during the period from 1999 to 2006 in Nanjing [ 24 ].…”
Section: Discussionsupporting
confidence: 92%
“…The proportion of CRO less susceptible N. gonorrhoeae isolates (CRO MIC ≥ 0.06 mg/L) was 17.86–50.5% during the period from 1999 to 2006 in Nanjing [ 24 ]. Chen et al reported that the proportion of isolates with a CRO MIC = 0.125 mg/L was 39.4% in 2007 and 11.3% in 2012 [ 25 ]. The proportion of CRO nonsusceptible isolates (MIC ≥ 0.125 mg/L) ranged from 22% to over 48% in Nanning in 2000–2012 [ 26 ], much higher than that detected in Shanghai.…”
Section: Discussionmentioning
confidence: 99%
“…The programme documented a statistically significant increase in cefixime resistance from 2009 (5.1 %) to 2010 (8.7 %), however after 2010 the cefixime resistance levels started to decrease to a low of 3.9 % in 2012 [ 29 , 30 ]. Similar decreases in the resistance to ESCs have also been documented in other regions [ 15 , 16 , 31 36 ].…”
Section: Introductionsupporting
confidence: 81%
“…As well as decreases in the level of resistance to ESCs in the EU/EEA from 2010 to 2012, decreases have also been observed in other regions with well-developed surveillance programmes globally [ 15 , 16 , 31 , 33 36 ]. Furthermore, despite some rare ESC treatment failures verified in recent years [ 3 – 14 ], the anticipated number of reported gonorrhoea treatment failures has not yet materialised, which could also be partly due to a lack of identification and under-reporting of treatment failures.…”
Section: Discussionmentioning
confidence: 93%
“…In jüngster Zeit wurden in Japan, Australien, Kanada, Südafrika und in einigen europäischen Ländern wie England, Frankreich, Spanien, Österreich und Schweden zunehmende Resistenzentwicklungen gegen Cefixim beobachtet [11,[16][17][18][19][20][21][22][23]. Auch bei der GO-Behandlung mit Ceftriaxon fanden sich in den letzten Jahren vermehrt Einzelfallberichte über ein Therapieversagen, wie beispielsweise in Australien, Japan, Slowenien und Schweden [23][24][25][26][27]. Studien des Gonococcal Resistance to Antimicrobials Surveillance Programme (GRASP) aus England zeigen zusätzlich, dass sich die Verbreitungen von Antibiotikaresistenzen bei NG-Infektionen je nach Risikogruppe unterscheiden [28].…”
unclassified